2012
DOI: 10.5562/cca2051
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Effect of PEG-1000-based Dicationic Ionic Liquid for N-hydroxyphthalimide-catalyzed Aerobic Selective Oxidation of Alkylaromatics

Abstract: Abstract. PEG 1000-based functional dicationic acidic ionic liquid (PEG 1000 -DAIL) was used for the first time as the reaction solvent for the N-Hydroxyphthalimide (NHPI)-cobalt acetate(Co(OAc) 2 ) catalyzed aerobic oxidations of alkylaromatics to the corresponding acids. It enhanced the efficient catalytic ability of NHPI: 99.9 % conversion of toluene with 99.5 % selectivity for benzoic acid could be obtained at 80 °C in 10 h and ethylbenzene was selectively oxidized to benzoic acid. Several alkylaromatics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Our results showed that the pyridinium salt group played a crucial role for the observed high performance in this catalytic system. Recently, oximes, structurally similar to NHPI, has been found to facilitate the oxidation of hydrocarbons catalyzed by NHPI and its derivatives [35][36][37]. Mechanistic study revealed that the corresponding N-oxyl radicals of oximes were produced easily due to its lower >NO H bond dissociation enthalpy (BDE) than that of NHPI.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the pyridinium salt group played a crucial role for the observed high performance in this catalytic system. Recently, oximes, structurally similar to NHPI, has been found to facilitate the oxidation of hydrocarbons catalyzed by NHPI and its derivatives [35][36][37]. Mechanistic study revealed that the corresponding N-oxyl radicals of oximes were produced easily due to its lower >NO H bond dissociation enthalpy (BDE) than that of NHPI.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its poor solubility in hydrocarbons, the processes are usually carried out in polar solvents, e.g., in acetic acid [7], acetonitrile [8], or benzonitrile [9]. The use of compressed CO 2 [10][11][12] and ionic liquids [11,[13][14][15][16][17][18] has also been reported. In order to use NHPI in industrial processes, it is necessary to develop efficient methods of its recovery and reuse.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Several examples have been reported on the use of ILs as solvents for NHPImediated oxidations of a wide range of substrates, [19,20] including the conversion of alkyl aromatic hydrocarbons, such as pxylene, toluene, EB, cumene and their derivatives, to the corresponding carboxylic acids. [21][22][23] Among the wide range of ILs commercially available, it was demonstrated that the imidazolium-based ones are particularly suitable for promoting aerobic oxidations, as they can accelerate the electron transfer from metal ions to O 2 by stabilization of the resulting superoxyl radical. [24][25][26][27] Recently, some of us reported the oxidation of cumene and other alkylaromatic hydrocarbons to hydroperoxides in the presence of various N-hydroxyimides, including NHPI, in a broad range of ILs composed of 1-alkyl-3-methylimidazolium cations and bis(trifluoromethylsulfonyl)imide ( OSO 3 ] anions.…”
Section: Introductionmentioning
confidence: 99%